The Use Of Online Learning Platforms On Student Classroom Engagement In Public Speaking - Oktavianus, Bryan (UKMC International Conference (UKMC IC) Proceedings, 2024)
Using a theoretical model with OPs as the independent variable, student learning satisfaction (LS) as the dependent variable, and learning quality (IP) and learning engagement (LE) as the mediating variables, this study investigates the effect of OPs on student engagement in the public speaking classroom. The study examines the frequency and motivations for using different online platforms, the perceived advantages of online learning, its impact on motivation, communication skills, and interaction with instructors, as well as recommendations for improvement. It gathers this data through a questionnaire-based survey given to college students. Results show that there is an increasing trend of using technology in public speaking instruction. Online resources improve students' motivation, communication abilities, and overall learning experience. Increasing the frequency of platform usage, improving content and interaction, and sboosting active engagement as well as providing a safe and supportive learning environment. For educators and policymakers looking to optimize the efficacy of online learning platforms in the teaching of public speaking, this study offers insightful information.